Molecular modeling on porphyrin derivatives as β5 subunit inhibitor of 20S proteasome. (June 2018) - Arba, Muhammad; Nur-Hidayat, Andry; Ruslin; Yusuf, Muhammad; Sumarlin; Hertadi, Rukman; Wahyudi, Setyanto Tri; Surantaadmaja, Slamet Ibrahim; Tjahjono, Daryono H.
Graphical abstract: Tetra-H2PyP in the binding pocket of β5 subunit of 20S proteasome. Highlights: The interaction between cationic porphyrin derivatives and β5 subunit of 20S proteasome was computationally investigated. MD simulation and binding free energy prediction were conducted. The predicted binding energies of mono-H2 PyP, bis-H2 PzP, and tetra-H2 PyP were comparable with that of a potential inhibitor, HU10. Abstract: The ubiquitin-proteasome system plays an important role in protein quality control. Currently, inhibition of the proteasome has been validated as a promising approach in anticancer therapy. The 20S core particle of the proteasome harbors β5 subunit which is a crucial active site in proteolysis. Targeting proteasome β5 subunit which is responsible for the chymotrypsin-like activity of small molecules has been regarded as an important way for achieving therapeutics target. In the present study, a series of porphyrin derivatives bearing either pyridine or pyrazole rings as meso -substituents were designed and evaluated as an inhibitor for the β5 subunit of the proteasome by employing molecular docking and dynamics simulations. The molecular docking was performed with the help of AutoDock 4.2, while molecular dynamics simulation was done using AMBER 14. All compounds bound to the proteasome with similar binding modes, and each porphyrin-proteasome complex was stable during 30 ns MD simulation as indicated by root-mean-square-deviation (RMSD) value. An analysis on protein residue fluctuation of porphyrin binding demonstrates that in all complexes, porphyrin binding produces minor fluctuation on amino acid residues. The molecular mechanics Poisson-Boltzmann surface area (MM-PBSA) free energy calculation shows that the binding affinities of mono-H2 PyP, bis-H2 PzP, and tetra-H2 PyP were comparable with that of the potential inhibitor, HU10. It is noted that the electrostatic interaction increases with the number of meso -substituents, which was favourable for porphyrin binding. The present study shows that both electrostatic and van der Waals interaction are the main force which controls the interaction of porphyrin compounds with the proteasome.